Effect of different protein sources in ensiled sugar beet pulp-based diets on the performance of fattening lambs - Benbati M.; El Hansali M.; El Azhari E.; Mounsif M.; Haddioui A.; Benjelloun B.; Keli A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The aim of this study was to compare the effects of using different sources of protein in ensiled sugar beet pulp-based diets on production performance of lambs. Eighteen Moroccan synthetic breed lambs “Dman*Boujaad” (19.7±1.07 kg initial body weight) were used to carry out this trial during 70 days preceded by a period of 15 days of adaptation to the experimental diets. Lambs were randomly assigned to three treatments (6 animals per treatment) and received a diet containing ensiled sugar beet pulp, barley straw, maize grain and three different protein sources: TTTS (sunflower meal), TTS (soybean meal) and Turea (urea). Lambs were weighed at the beginning and at the end of the trial, and fortnightly in order to determine dry matter intake (DMI), average daily gain (ADG), feed conversion ratio (FCR) and feeding cost. The average daily gain was affected by the type of protein source (P<.0001). It was 173.4, 244.5 and 91.1 g/d for TTTS, TTS and Turea, respectively. Feed conversion ratio (kg DMI/kg ADG) was 6.65, 4.70 and 9.21 for TTTS, TTS and Turea, respectively. The feeding cost (Moroccan dirham (MAD)/kg ADG) was 20.5, 16.3 and 26.6 for TTTS, TTS and Turea, respectively. The inclusion of soybean meal in ensiled sugar beet pulp-based diets improves fattening performance of lambs.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)